PENGARUH MODEL SAINS TEKNOLOGI MASYARAKAT TERHADAP HASIL BELAJAR TEMATIKSISWA KELAS IV SEKOLAH DASAR - Maru Septiadi; Kartono Kartono; Endang Uliyanti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis study aimed to analyze the effect of science technology society model to fourth grade students' thematic study result atSekolah Dasar Negeri 12 Pontianak Kota. This research used experimental method with a quasi experimental form and nonequivalent control group design. The population of this study was all fourth grade students of Sekolah Dasar Negeri 12 Pontianak Kota with total 47 students. The sampling technique used probability sampling with simple random sampling type. Data collection techniques used measurement techniques. The research instrument used was a written test with multiple choice form.Based ondata analysis result, average score of post-test in the experiment class and the control class were 65 and 57,826.The result of t-test obtained tcount = 2,043 and ttable = 2,0105 (α = 5%; db = 44). Because tcount (2,043) > ttable (2,0105), its mean Ha accepted and H0 rejected. The effect size result was0,57 with medium criteria. The conclusion in this study was the science technology model effected to fourth grade students’ thematic study result at Sekolah Dasar Negeri 12 Pontianak Kota. Keyword:           The Effect, Science Technology Society Model, Study Result, Thematic Learning